Anticancer effects of metformin and its potential use as a therapeutic agent for breast cancer. (June 2011) - Guppy, Amy; Jamal-Hanjani, Mariam; Pickering, Lisa
Metformin is an orally available, biguanide derivative that is widely used in the treatment of Type 2 diabetes. Recent preclinical data have demonstrated that it can also act as an anticancer agent by activation of AMPK and subsequent inhibition of mTOR. Metformin is currently being investigated in several Phase II/III clinical trials. This article will review the current evidence for its mechanism of action, efficacy in preclinical and clinical models, and toxicity. Ongoing and planned studies evaluating the impact of metformin on breast cancer outcomes are also discussed.